Gramática Discursivo-Funcional e os estudos tipológicos: um exercício de análise das línguas indígenas do Brasil - Dall'Aglio-Hattnher, Marize Mattos [UNESP] (My University, 2012)
In this paper, I intend to show how the Functional Discourse Grammar might contribute to typological studies, composing a coherent model for the kind of language description required by a research of this nature. To examine the relationship between the typological and functionalist studies, I discuss some theoretical and methodological issues that arose in the analysis of the evidentiality expression in a set of native languages of Brazil.

Neste trabalho, procuro mostrar como a Gramática Discursivo-Funcional pode contribuir para os estudos tipológicos, constituindo-se como um modelo coerente para o tipo de descrição linguística que sustenta as investigações dessa natureza. Para analisar a relação entre os estudos tipológicos e os estudos funcionalistas, discuto algumas questões teórico-metodológicas que surgiram na análise da expressão da evidencialidade em um conjunto de línguas nativas do Brasil.
Functional Discourse Grammar and typological studies: an exercise in the analysis of native languages of Brazil
Keywords: tipologia; Gramática Discursivo-Funcional; evidencialidade; typology; Functional Discourse Grammar; evidentiality